The Relations Among Physical Indicators, Cognitive Status, Community Participation, and Depression of the Frail Male Elderly in Taiwan. Issue 6 (November 2020) - Lin, Hsiang-Chun; Chang, Shu-Fang; Chen, Yen-Hung
This study explored the basic attributes, physiological indices, cognitive states, and community participation of older male outpatients with frailty for predicting depression. Questionnaires were collected using purposive sampling from a medical clinic in a teaching hospital in northern Taiwan. One hundred and ninety frail men enrolled as participants. The results revealed that older male adults with frailty, the age, residence, income, self-reported health status, alcohol consumption, total instrumental activities of daily living (IADL) scores in physiological indices, IADL grouping, cognitive state score, each Mini-Mental State Examination category, and involvement and dedication scores exhibited statistical differences from depression scores. Depression determinants, such as an excellent and normal self-reported health status and IADL total score, could predict the depression status of male older adults with frailty. Nursing personnel should assess the self-reported health status and self-care ability of male older adults with frailty early to prevent or delay geriatric depression.